Clinical trials optimizing investigator and self‐collection of buccal cells for RNA yield. Issue 1 (18th January 2021) - Geiger, Jessica L.; Cedars, Elizabeth D.; Zang, Yan; Normolle, Daniel P.; Li, Hua; Grandis, Jennifer R.; Centuori, Sara; Johnson, Daniel E.; Bauman, Julie E.
Abstract: Objective: Buccal cells are an ideal surrogate tissue for studying biologic effects of carcinogens or drugs, however inherent fragility and salivary RNAses limit RNA yield. We conducted healthy volunteer trials to optimize collection conditions. Methods: We conducted: (a) a single‐arm crossover study evaluating four test conditions on RNA yield by buccal cytobrush; (b) a single‐arm prospective study evaluating RNA yield by investigator vs self‐collection. Results: Antecedent toothbrushing, time of day, and number of cytobrush strokes did not significantly impact RNA yield. RNA yield was doubled by using 2 vs 1 cytobrush per buccal surface ( P = .0054). Self‐collection of buccal cells for RNA was feasible; 36 of 50 (72%) samples passed quality control. Conclusion: RNA yield was doubled by using two cytobrushes per buccal surface. Healthy volunteers can self‐collect sufficient buccal RNA for gene expression studies. Techniques from these pragmatic trials could enhance availability of a limited tissue for serial biomarker measurements. Level of Evidence: 1b—Prognosis Study (Individual prospective cohort study). Abstract : Buccal cells are an ideal surrogate tissue for studying biologic effects of carcinogens or drugs, however inherent fragility and salivary RNAses limit RNA yield. We conducted two clinical trials evaluating various collection conditions to optimize RNA yield. We observed that yield is doubled by using 2 cytobrushes per buccal surface and that self‐collection is both feasible and sufficient for buccal mRNA for gene expression studies.